The Effect of Metacognition Regulation Evaluation On Medical Student Progress: Metacognition Regulation Evaluation on Medical Student Progress - Iqbal, Saba; Sukhera, Shazia; Aslam, Fatima; Hayat Sukhera, Khyzer; Zafar, Arifa (Pakistan Journal of Health Sciences, 2022)
Cognition is the scientific term referring to the mental processes involved in gaining an understanding of knowledge including, judging, thinking, reasoning, knowing, remembering, and problem-solving. Objective: To observe metacognition's impact on medical students' academic achievement. Methods: It was a cross-sectional analytical study. Three medical colleges were surveyed to obtain data from second-year medical students. The data from the Metacognitive Awareness of Reading Strategies Inventory (MARSI) and each student's first-year academic achievement information were collected from January to June 2021. A simple random sampling procedure. Academic performance was a dependent variable, while the metacognitive score was an independent variable. Three hundred thirty-two students participated in the survey. Results: With a correlation coefficient value of 0.257, the findings indicated a significant link between metacognition and academic success (p 0.01). Metacognition levels among medical students from various colleges are nearly identical. Conclusions: Current study findings have shown that all three dimensions are positively and strongly correlated to each other.